Differential treatment of female defendants: does criminal history moderate the effect of gender on sentence length in federal narcotics cases? - Tillyer, Rob (Criminal justice and behavior, 2015)
Past research indicates that men and women are treated differently at the sentencing phase, but the specifics of this relationship have not been fully explicated. The current study draws on the chivalry and evil woman hypotheses to examine how a defendant?s gender may interact with criminal history to affect sentence length in federal narcotics cases. Results indicate that gender?s effect on sentence length is nuanced, complex, and dependent on a defendant?s criminal history score; thus, conditional support is found for both the chivalry and evil woman hypotheses. Specifically, female defendants with lower criminal history scores received more lenient treatment (relative to male defendants) whereas those with higher criminal history scores received more severe sentences. These findings suggest that further exploration of interactions between extralegal and legal factors is necessary to uncover the complex ways in which gender influences court outcomes.